Association of Serum Calcium Levels with Menopausal Status and Risk of Health Outcomes Post-COVID-19 Vaccination: A Comparative Study - Tawfeeq, Shaymaa; Jabbar Tauma, Rusul; Mohammed Albobaqer, Aseel Abdulameer; G. Yousif, Maitham (Journal of Neonatal Surgery, 2025)
The function of menopausal status and serum calcium level with different health outcomes has been taken into close consideration, but the influence on health after vaccination for covid-19 has been little discussed. The present research is aimed at the serum calcium levels across menopausal stages and offtakes the health problems that such vaccination can cause. The sample was female; 235 patients were aged 17–46 years with most of them domiciled in urban areas. The serum calcium levels measured in both groups of women, before and after the change in menstrual cycle were determined and the values were compared with each other. The area under the curve analysis was utilized in the study for the purpose of assessing for menopause the ability of serum calcium levels to determine the disease. The control group of premenopausal women was employed for instance what the normal levels are. The next step was the introduction of micronutrient-rich foods. In postmenopausal women, evidence from serum calcium levels indicates a significant lowering of levels compared to premenopausal women, which signifies a notable deficiency. As far as a direct response on calcium deficit is regarded, the value increase from the level of -15.05 was obvious for post-menopausal status, while pre-menopause offered protection. The calcium of serum test received the best scores for predicting menopause mechanism. It had a sensitivity percentage until 94% and a specificity percentage until 92%. On the other hand, women who barely had more than a score of 4 were at an 11.75 times risk of going through menopause. It can prove the existing correlation between serum calcium levels and menopausal status, as well as the effect on COVID-19 vaccination efficiency. The individualization of the action plan on the basis of determining species-specific needs in calcium levels revealed among women in the menopausal age by outlining the prevention strategies as well as identifying possible insufficiency and other aggravated cases among this group. The results of this study contribute to the already existing knowledge of post-vaccination health hazards. It also emphasizes the fact that the general perspective on healthcare whenever there is COVID-19 immunization becomes more balanced.